2019
DOI: 10.1111/1756-185x.13507
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic nutritional index is associated with disease severity and relapse in ANCA‐associated vasculitis

Abstract: Aim The prognostic nutritional index (PNI), calculated by serum albumin and peripheral blood lymphocyte count, is considered to reflect immune‐related nutritional status. In this study, we first investigated the clinical significance of PNI in patients with antineutrophil cytoplasmic antibody‐associated vasculitis (AAV). Method Medical records of 160 patients classified as AAV from October 2000 to September 2017 were reviewed. We calculated the Birmingham vasculitis activity score (BVAS) and collected laborato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 32 publications
1
9
0
Order By: Relevance
“…Studies have reported that the decrease in Alb is suitable for assessing the severity of disease in rheumatoid arthritis, systemic lupus erythematosus, and ulcerative colitis [ 25 28 ]. Interestingly, the observations from this study confirmed the previously obtained data of our group, which showed hypoalbuminemia at AAV diagnosis was associated with disease activity and lymphocyte count [ 29 ]. Furthermore, the correlation coefficient between BVAS and Alb (BVAS vs. Alb: r = -0.664; 95% CI: -0.787, -0.492; p<0.001) was higher than that of BVAS with ESR (BVAS vs. ESR: r = 0.576; 95% CI: 0.375, 0.725; p<0.001) and BVAS with CRP (BVAS vs. CRP: r = 0.416; 95% CI: 0.180, 0.608; p = 0.001).…”
Section: Discussionsupporting
confidence: 92%
“…Studies have reported that the decrease in Alb is suitable for assessing the severity of disease in rheumatoid arthritis, systemic lupus erythematosus, and ulcerative colitis [ 25 28 ]. Interestingly, the observations from this study confirmed the previously obtained data of our group, which showed hypoalbuminemia at AAV diagnosis was associated with disease activity and lymphocyte count [ 29 ]. Furthermore, the correlation coefficient between BVAS and Alb (BVAS vs. Alb: r = -0.664; 95% CI: -0.787, -0.492; p<0.001) was higher than that of BVAS with ESR (BVAS vs. ESR: r = 0.576; 95% CI: 0.375, 0.725; p<0.001) and BVAS with CRP (BVAS vs. CRP: r = 0.416; 95% CI: 0.180, 0.608; p = 0.001).…”
Section: Discussionsupporting
confidence: 92%
“…Our team had previously evaluated prognostic nutritional index, an index that reflects nutritional status, in patients with AAV and revealed that it correlated with the BVAS and predicted relapse. 30 Similarly, we demonstrated that a poor nutritional status was associated with a higher BVAS, and that it was a risk factor for ESRD occurrence. 31 One explanation for these findings is that underweight patients are at an increased risk of low muscle mass, 32 , 33 and muscle mass is associated with chronic kidney disease.…”
Section: Discussionmentioning
confidence: 52%
“…The exact mechanism underlying these associations is unclear. Our team had previously evaluated prognostic nutritional index, an index that reflects nutritional status, in patients with AAV and revealed that it correlated with the BVAS and predicted relapse 30 . Similarly, we demonstrated that a poor nutritional status was associated with a higher BVAS, and that it was a risk factor for ESRD occurrence 31 .…”
Section: Discussionmentioning
confidence: 72%
“…Multiple biomarkers of disease activity in AAV have been proposed, including platelet count [31], lung involvement [32], and prognostic nutritional index [33]. A rise in or persistence of ANCAs during remission is only modestly predictive of future disease relapse [34].…”
Section: Discussionmentioning
confidence: 99%